2017
DOI: 10.1007/s13197-017-2503-1
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid content and antioxidant activity of different types of beers available in Hungarian retail

Abstract: In this study 40 Hungarian retail beers were evaluated for folic acid content, antioxidant profile and physicochemical parameters. The physicochemical parameters, folic acid content and antioxidant activity of alcohol-free beers were the lowest. Folic acid content of beers aged with sour cherries showed high values, more than 0.4 mg/l and an alcohol-free beer-based mixed drink made with lemon juice contained more than 0.2 mg/l of folic acid. Dark beers and beers aged with sour cherries had the highest antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(23 reference statements)
2
9
0
1
Order By: Relevance
“…In this sense, an extensive study was carried out by Zhao et al in 2010 [47], in which 34 lager beers were analyzed and where TPC ranged between 152 and 339 mg GAE/L. Other later studies on Polish, Belgian, Serbian, Indian or Hungarian beers agree with that study [60,66,72,74,75] In general, ale beers present higher TPC than lagers [76]. In a comparative study between different Brazilian beers, it was observed that brown ale beers presented higher TPC than lager beers and also higher antioxidant properties [69].…”
Section: Total Phenolic Content Measurementmentioning
confidence: 66%
See 3 more Smart Citations
“…In this sense, an extensive study was carried out by Zhao et al in 2010 [47], in which 34 lager beers were analyzed and where TPC ranged between 152 and 339 mg GAE/L. Other later studies on Polish, Belgian, Serbian, Indian or Hungarian beers agree with that study [60,66,72,74,75] In general, ale beers present higher TPC than lagers [76]. In a comparative study between different Brazilian beers, it was observed that brown ale beers presented higher TPC than lager beers and also higher antioxidant properties [69].…”
Section: Total Phenolic Content Measurementmentioning
confidence: 66%
“…Several studies have shown that fruity beers present high phenolic content, since fruits are an important source of phenols. Values of 1033 mg GAE/L, measured by FC method, have been reached for a Belgian beer made with elderberries [66]. High values are also obtained for beers made with persimmons [67] or goji berries [68].…”
Section: Total Phenolic Content Measurementmentioning
confidence: 85%
See 2 more Smart Citations
“…Several authors postulate that beer ingestion protects from oxidative stress as a result of the high beer content of antioxidants [62,63,64,65]. Thus, these antioxidant compounds show protective effects in several experimental models.…”
Section: Discussionmentioning
confidence: 99%